Evaluasi Kinerja dan Kemampuan Keuangan Pemerintah Daerah Kota Mataram di Masa Pandemi Covid-19 - HELMIN SAFITRI; ELIN ERLINA SASANTI; NURABIAH - (Pusat Penelitian dan Pengabdian pada Masyarakat Sekolah Tinggi Ilmu Administrasi (STIA) Mataram, 2022)
This study aims to determine the performance and financial capacity of the local government of Mataram City during the COVID-19 in 2019 to 2020 based on PMK Number 22/PMK.02/2021 to assess financial performance and Minister of Home Affairs Regulation Number 19 of 2020 to assess financial capability.The research design is descriptive qualitative with data collection techniques through documentation and research interview. The results of the study indicate that the financial performance aspect of the achievement (output) of the independence ratio is in the consultative criteria, while the aspect of budget absorption and the consistency of budget absorption on the ratio of the degree of fiscal decentralization is at a moderate level. The results also show that the local government of Mataram City is very effective in realizing local revenue revenue according to the predetermined target, but is very inefficient in managing the amount of costs incurred to obtain revenue. In terms of the activity ratio, the local government of Mataram City mostly allocates regional expenditures to operating expenditures compared to development expenditures. Meanwhile, in terms of financial capacity, the local government of Mataram City obtained an average share of 25% and growth of 0.67% in terms of the suitability of budget planning documents, allocation of APBD expenditures, and budget absorption. Regarding regional financial conditions, the results of the study show that the local government of Mataram City is not in an ideal position and has not been able to implement regional autonomy perfectly.